تفسير سورة البقرة تفسيرا مقارنا من الآية 124 إلى الآية 164 - القائد, ضياء الحق; بالخير, عبد الحليم; ولابي, منير (University of Eloued-جامعة الوادي, 2022)
يعد التفسير المقارن لونا من ألوان التفسير الذي يهتم بالآيات المختلف فيها اختلافا حقيقيا معتبرا سواء كان اختلاف تنوع أو تضاد -على الصحيح-، وهذا اللون يعتبر حديث التأليف فيه تنظيرا كفن مستقل وقديما من جهة التطبيق والممارسة العملية؛ إذ تعد تطبيقات المفسرين في كتبهم هي المرجع الأساس للباحث في التفسير المقارن وتختلف مراتب المفسرين من حيث ممارستهم للمقارنة بين الأقوال التفسيرية المختلفة بين مستقل ومستكثر، فيعد الطبري أول وأكثر المفسرين سخاء في هذا الباب، ثم تتابع من بعده جملة من المفسرين في ذلك كل يغلب عليه العلم الذي يشتغل به، فالفقيه يغلب عليه في تفسيره التعرض للمسائل العلمية، والنحوي كذلك، والبلاغي كذلك وهكذا.وقد جعلنا لبحثنا هذا أربعة مباحث تناولنا في كل مبحث آية من سورة البقرة اختلف في تفسيرها وذلك ما بين الآية 124 إلى 164, قارنًا فيها بين تلك الأقوال وصولا إلى القول الأولى والأرجح.Comparative Tafssir is one of the types of the Tafssirs, which is concerned with the different verses in which there is a real difference in consideration, whether it is a difference of diversity or contradiction to the correct one, and this type is considered new to theoretically as an independent art and in the past in terms of application and practical practice, as the applications of interpreters in their books are the main reference for the researcher in the comparative Tafssir and the ranks of the interpreters differ in terms of their practice of comparison between The various explanatory sayings between independent and multiplied, so Al-Tabari is the first and most generous interpreter in this section, and then a number of interpreters follow in it all that is overpowered by the knowledge that he works with, so the jurist dominates him in his interpretation of exposure to scientific issues, grammatical as well, and rhetoric as well and so on. and we have discussed these 4studies and its interpretations of surat al-baqarah and its differences and that is between verse 124 to164 .We compared these sayings arriving at the first and nost likely saying.
مذكرة ماستر
Keywords: سورة البقرة - تفسيرًا - مقارنًا; Surat Al-Baqarah - Interpretation - Comparative